Kartografia domu. O twórczości Barbary Gawryluk - Małgorzata Wójcik-Dudek (Paidia i Literatura, 2021)
The article attempts to present one of the extremely important themes in the work of Barbara Gawryluk, which is emigration and the creation of a new home abroad. The author of the article, referring to selected works by the Krakow writer, tries to present how Gawryluk constructs the motif of a journey and the topos of the home and read the meaning that the writer gives to these spaces. The researcher notes the differences between the literary images of emigration caused by difficult economic conditions and the images of refugees forced to leave their homeland to save their lives.